Who Owns the Land: Perspectives from Uganda - Bomuhangi, Allan; Doss, Cheryl; Meinzen-Dick, Ruth (United States Agency for International Development (USAID), 2012)
Rapid growth of demand for agricultural land is putting pressure on property rights systems, particularly in Sub-Saharan Africa where customary tenure systems have provided secure land access. Patterns of gradual, endogenous change toward formalization are being challenged by rapid and large-scale demands from outsiders. The sudden rise in global food prices in 2007-2008 precipitated increased demand for agricultural land from the Gulf countries, China and India, all of which are dependent on food imports. As these countries began seeking to secure their food supplies, European demands for biofuels and speculative demand from other investors also grew, thus increasing pressure on agricultural land in Africa.